Model Rancangan Pembelajaran Kooperatif Learning Team Game Tournament (TGT) pada Pelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Nabilla Fuji Astuti; Agus Suryana; E.Hamzah Suaidi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
This research aims to describe the Cooperative Learning Design for the Learning Team Game Tournament (TGT) in the 6th grade Social Sciences Lesson on Export and Import Activities, explaining the advantages of the Cooperative Learning Design for the Learning Team Game Tournament (TGT) in the 6th grade Social Sciences Lesson on Export and Import Activities. This research method uses the library method by analyzing various books and journals related to the Cooperative Learning Design Learning Team Game Tournament (TGT) in Social Studies Lesson 6th grade Materials for Export and Import Activities. The conclusions conclude that: The TGT learning model is a learning activity that involves heterogeneous group learning both from background and academic achievement and taking games and systematic tournaments or competitions that will provide scores, standings, and champions for individuals or groups who succeed in getting the best score to foster a sense of fun and motivation in learning which aims to improve learning outcomes, improve memory, make students accustomed to using high-level reasoning. The self-confidence is high, reduce student deviant behavior in the classroom, for example disturbing friends, increased student motivation, improve students' understanding of certain subjects, increase kindness, sensitivity, and tolerance, both tolerance between students and tolerance between students and teachers. The steps of the TGT Learning Model are as follows: Presentation in class (classical), study together in teams, Games consist of questions with relevant content, after forming a team, children start competing in tournaments, calculating scores by seeing how many students can collect question cards from players who have done. Keywords: TGT (Team Games Tournament) Cooperative Learning Model Design, Social Science Lessons